Evolutionary development of mother–child scaffolding for moral comprehension - Beck, Robert J. (Frontiers in Psychology, 2024)
An evolutionary developmental study used an experimental recursive narrative ecological niche in which mother-child (5s) scaffolded pairs, compared with unassisted controls, independently viewed, discussed, and children retold a realistic fictional family video story representing a father-daughter emotional conflict about the girl's risky behavior violating harm/care and fairness/justice moral foundation norms. A microgenetic analysis was conducted of a selected smart variant pair that responded with high adaptive fitness to the niche by employing developmentally advanced cooperative scaffolding tools. The conversational ecosystem phase featured repeated maternal theory-oriented why-questions and coordinated child causal responses forming a joint epistemic investigation supporting the participating child's moral comprehension of the characters' responsibilities and motives. The pair used quasi-justice procedures for gathering evidence, judging and creating moral attributes of the characters. The conversational mechanism was supported through mutual mindreading, mental time travel, and empathic communications as the participants interacted simultaneously with each other and the story characters. A narrative ecological scaffolding theory formulated a mother-child standard for cooperative epistemic scaffolding. In a future direction, a training program would adapt a Zone of Proximal Development method to instruct comparable parent-child pairs.